Biology and ecology of the world’s largest invertebrate, the colossal squid (Mesonychoteuthis hamiltoni): a short review - Rosa, Rui (2020)
The colossal squid Mesonychoteuthis hamiltoni (Robson 1925) is the largest (heaviest) living invertebrate and although it is preyed upon by many top predators, its basic biology and ecology remain one of the ocean’s great mysteries. The present study aims to review the current biological knowledge on this squid. It is considered to be endemic in the Southern Ocean (SO) with a circumpolar distribution spreading from the Antarctic continent up to the Sub-Antarctic Front. Small juveniles (<40 mm mantle length) are mainly found from the surface to 500 m, and the late juvenile stages are assumed to undergo ontogenetic descent to depths reaching 2000 m. Thus, this giant spends most of its life in the meso- and bathypelagic realms, where it can reach a total length of 6 m. The maximum weight recorded so far was 495 kg. M. hamiltoni is presently reported from the diets of 17 different predator species, comprising penguins and other seabirds, fishes and marine mammals, and may feed on various prey types, including myctophids, Patagonian toothfish, sleeper sharks and other squid. Stable isotopic analysis places the colossal squid as one of the top predators in the SO. It is assumed that this squid is not capable of high-speed predator–prey interactions, but it is rather an ambush predator. Its eyes, the largest on the planet, seem to have evolved to detect very large predators (e.g., sperm whales) rather than to detect prey at long distances. The study of this unique invertebrate giant constitutes a valuable source of insight into the biophysical principles behind body-size evolution.